Dynamic cardiovagal response to motion sickness: A point-process heart rate variability study - LaCount, L T; Napadow, V; Kuo, B; Park, K; Kim, J; Brown, E N; Barbieri, R (2009 36th Annual Computers in Cardiology Conference (CinC), 2009)
A visual display of stripes was used to examine cardiovagal response to motion sickness. Heart rate variability (HRV) was investigated using dynamic methods to discern instantaneous fluctuations in reaction to stimulus and perception-based events. A novel point process adaptive recursive algorithm was applied to the R-R series to compute instantaneous heart rate, HRV, and high frequency (HF) power as a marker of vagal activity. Results show interesting dynamic trends in each of the considered subjects. HF power averaged across ten subjects indicates a significant decrease 20s to 60s following the transition from ¿no nausea¿ to ¿mild.¿ Conversely, right before ¿strong¿ nausea, the group average shows a transient trending increase in HF power. Findings confirm gradual sympathetic activation with increasing nausea, and further evidence transitory increases in vagal tone before flushes of strong nausea.